Find the exact sum of n = 1 ∑ ∞ n 4 1 = 1 + 2 4 1 + 3 4 1 + 4 4 1 + ⋯ also known as ζ ( 4 ) , where ζ ( s ) is the Riemann zeta function .
Hint
: Follow Euler's famous
solution of the Basel problem
.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Problem Loading...
Note Loading...
Set Loading...
As before:
x sin ( x ) = 1 − 3 ! x 2 + 5 ! x 4 − 7 ! x 6 + . . . = ( 1 − π 2 x 2 ) ( 1 − 4 π 2 x 2 ) ( 1 − 9 π 2 x 2 ) . . .
Now, substituting ix for x yields:
i x sin ( i x ) = 1 − 3 ! ( i x ) 2 + 5 ! ( i x ) 4 − 7 ! ( i x ) 6 + . . . = ( 1 − π 2 ( i x ) 2 ) ( 1 − 4 π 2 ( i x ) 2 ) ( 1 − 9 π 2 ( i x ) 2 ) . . .
Or
i x sin ( i x ) = 1 + 3 ! x 2 + 5 ! x 4 + 7 ! x 6 + . . . = ( 1 + π 2 x 2 ) ( 1 + 4 π 2 x 2 ) ( 1 + 9 π 2 x 2 ) . . .
So multiplying the first equation by the second yields:
1 + ( 3 ! x 2 − 3 ! x 2 ) + ( 5 ! x 4 − 3 ! 2 x 4 + 5 ! x 4 ) + . . . = ( 1 − π 2 x 2 ) ( 1 + π 2 x 2 ) ( 1 − 4 π 2 x 2 ) ( 1 + 4 π 2 x 2 ) ( 1 − 9 π 2 x 2 ) ( 1 + 9 π 2 x 2 ) . . .
1 − 9 0 x 4 + . . . = ( 1 − π 4 x 4 ) ( 1 − 1 6 π 4 x 4 ) ( 1 − 8 1 π 4 x 4 ) . . .
1 − 9 0 x 4 + . . . = 1 − π 4 x 4 ( 1 4 1 + 2 4 1 + 3 4 1 + . . . ) + . . .
equating the x 4 terms:
− 9 0 x 4 = − π 4 x 4 ( 1 4 1 + 2 4 1 + 3 4 1 + . . . )
So
9 0 π 4 = 1 4 1 + 2 4 1 + 3 4 1 + . . .